Isolation and Characterization of Thermostable Organic Solvent Tolerant Protease from Bacillus Subtilis Isolate Rand - Abusham, Randa Abdelkareem (2009)
Currently, thermostable and organic solvent tolerant protease is not available in local and global market. In this research screening and isolation of thermostable and organic solvent tolerant protease from bacteria from spring water and contaminated soils from Selayang, Batang kali and Port Dickson, Malaysia were carried out. Nine isolates were positive on skim milk agar 10 (%). A newly isolated soil bacterium, Bacillus subtilis isolate Rand, which exhibited an extracellular protease activity, was identified based on 16S rRNA analysis (GenBank EU233271). Isolate Rand was isolated from contaminated soils from Port Dickson and showed the highest activity (34.9 U/ml). The crude protease activity was enhanced by n- hexadecane (log P 8.8) with 1.5 fold, n-tetradecane (log P 7.6) with 1.5 fold, n-dodecane (log P 6.0) with 1.5 fold, n-decane (log P 5.6) with 2 fold, n-hexane (log P 3.5) with 1.4 fold, p-xylene (log P 3.1) with 1.3 fold, toluen (log P 2.5) with 1.2 fold, benzene (log P 2.0) with 1.9 fold and butanol (log P 0.80) with 1.01 fold. Optimum activity of the crude enzyme was exhibited at 60oC. The enzyme appeared to be stable and retained its full activity after 30 minutes incubation from 4 to 55oC, while 81% of the activity was still retained at 60˚C. Further optimization studies were carried out to determine the best protease production condition. Maximum protease production was achieved when grown in 50 mL M2 medium (pH 7.0). Inoculum size of 5%(v/v) proved to be the best for protease production, with an optimum temperature of 37˚C, when grown under shaking condition of 200 rpm. All carbon sources tested decreased protease production, except lactose and melibiose whereby protease production was improved. Tryptone and ammonium heptamolybdate were found to be the best organic nitrogen and inorganic nitrogen sources, respectively. Protease production was stimulated by l-lysine and calcium. Protease from the Bacillus subtilis isolate Rand was purified using a combination of two purification steps, hydrophobic interaction chromatography on Octyl-Sepharose and gel filtration. Rand protease was purified by 19.3 fold purification and 60.5% recovery. Purified protease migrated as a single band with a molecular mass of ~28 kDa on SDSPAGE. The purified protease hydrolyzed azocasein at optimum temperature of 60ºC. However, the enzyme lost its activity with a half life of more than 20 min at 60 and 65ºC. The optimum activity of the protease was observed at pH 7.0 and it was stable in the pH range of pH 6.5 to 10. Purified Rand protease exhibited high stability in the presence of ndodecane (log P 6.6), diethylether (log P 4.3), p-xylene (log P 3.1), toluene (log P 2.5), benzene (log P 2.0), acetone (log P 0.23), butanol (log P 0.8) and ethanol (log P 0.24). The protease activity was completely inhibited by phenylmethanesulfonyl fluoride PMSF while 43 and 30% reduction of protease activity was observed in the presence of ethylene diamine tetraacetic acid EDTA and 1,4-Dithio-DL-threitol DTT, respectively. Protease activity retained about 95% and 63% in the presence of aminopeptidases (Bestatin) and aspartic proteases inhibitor (pepstatin A). Among the metal ions, Zn2+ was found to stimulate protease activity by 175%. Protease activity was enhanced by 105%, 112% and 105%, respectively Na+, K+ and Li+. For substrate specificity, Rand protease was able to hydrolyze several native proteins such as casein, haemoglobin, albumin and azocasein.